COMPREHENSIVE REVIEW OF MANUAL THERAPY TECHNIQUES IN ASSESSING EFFICACY, INDICATIONS, AND CLINICAL APPLICATIONS IN PHYSICAL THERAPY - Hamad Dhafer Ali Al Obaya, Abdullah Nasser Ali Alyami, Hussain Mana Hussain Al Jafer, Mohammed Muidh Abdullah Alyami, Ghanem Mohammed Alabbas, Mohammed Hussain Saleh Alzabid, Hassan Yahya Mohammed Moafa, Saleh Mahdi Mani Alyami, (Chelonian Research Foundation, 2022)
Manual therapy methods are one of the main techniques used in physical therapy, in which a physical therapist utilizes calipered techniques of the hand with the main aim of enhancing the performance of the muscles and reducing pain. This all-encompassing review explores the level of effectiveness, application, and clinical relevance of manual therapy techniques in physiotherapy. The article encompasses a comprehensive analysis of the current literature on manual therapy for various musculoskeletal diseases. This will include findings on the effectiveness of manual therapy for the mentioned cases, the evidence supporting the use of manual therapy, and insights into its clinical application. Furthermore, suggestions about how manual therapy techniques can be used more efficiently to benefit physical therapy care are also explored. Keywords, manual therapy, physical therapy, and musculoskeletal conditions; clinical applications.